Penggunaan Shuujoshi Kana dan Kashira Dalam Drama Seri Itazurana Kiss-Love in Tokyo Season I Episode 01-16 - Sridayati '; Sri Wahyu Widiati; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to describe how to use the final particle (shuujoshi) kana and kashira in Japanese language drama by using sociolinguistic approach. Shuujoshi are particles (joshi) used at the end of a sentence or at the end of the sentence to express the speaker expression, prohibition, questions or doubts, expectations, or request, confirmation, orders, and so on. The particles included shuujoshi group is ka, kashira, to / kke, nee, no, wa, ze, zo, kana, naa, yo, tomo, sa, and ne. The method used is descriptive qualitative method. Shuujoshi kana and kashira associated with a variety of Japanese. Kana commonly used by both men and kashira worn by women. As the times there was no significant difference between the use shuujoshi kana and kashira. Data were analyzed as a number of research data 14 data each 7 data kana and 7 data kashira. Selection data is based on data relating to the speaker and the person said, which also in terms of age, gender, social class and the relationship between the speaker and the person said.Keywords : Shuujoshi, Kana, Kashira, Variety of Japanese, Sosiolinguistik.